Rola regionalnych izb obrachunkowych w procedurze uchwalania i kontroli wykonania budżetu jednostek samorządu terytorialnego - Sawicka, Krystyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Regional accounting chambers as bodies of supervision and control of local self-government’s financial management perform their tasks according to the principles stipulated by the binding legal regulations. Their participation in the procedure of passing the budget and supervision of its implementation consists in issuing opinions, which constitute the core of the chambers’ control activity. The opinions concern the following: the draft of the budget bill, financing budget deficit, information on the implementation of the budget in the first half year, the auditing committee’s motion concerning the vote of approval and the resolution of the decision-making body withdrawing the approval for the self-government unit’s board. Opinions concerning consecutive stages of budget procedure and the supervision of implementation of the budget are issued periodically and as such they constitute a type of continuous supervision executed at certain intervals, which considerably increases its efficiency. The fact that the issued opinions mainly concern certain types of activity of local self-government bodies preceding the moment of passing final resolutions thus constituting ex-ante control increases their significance in creating the lawful basis for financial management and its supervision. Ex-ante control prevents undertaking unlawful activity, which is decisive for its greater effectiveness.
Keywords: regionalne izby obrachunkowe; jednostki samorządu terytorialnego; nadzór nad wykonaniem budżetu; budżet gminy